H-ferritin and CD68+/H-ferritin+ monocytes/macrophages are increased in the skin of adult-onset Still's disease patients and correlate with the multi-visceral involvement of the disease. (28th July 2016) - Ruscitti, P; Cipriani, P; Ciccia, F; Di Benedetto, P; Liakouli, V; Berardicurti, O; Carubbi, F; Guggino, G; Di Bartolomeo, S; Triolo, G; Giacomelli, R
Summary: Adult-onset Still's disease (AOSD) patients may show an evanescent salmon-pink erythema appearing during febrile attacks and reducing without fever. Some patients may experience this eruption for many weeks. During AOSD, exceptionally high serum levels of ferritin may be observed; it is an iron storage protein composed of 24 subunits, heavy (H) subunits and light (L) subunits. The ferritin enriched in L subunits (L-ferritin) and the ferritin enriched in H subunits (H-ferritin) may be observed in different tissues. In this work, we aimed to investigate the skin expression of both H-and L-ferritin and the number of macrophages expressing these molecules from AOSD patients with persistent cutaneous lesions. We observed an increased expression of H-ferritin in the skin, associated with an infiltrate in the biopsies obtained from persistent cutaneous lesions of AOSD patients. Furthermore, a positive correlation between H-ferritin skin levels as well as the number of CD68 + /H-ferritin + cells and the multi-visceral involvement of the disease was observed. Our data showed an increased expression of H-ferritin in the skin of AOSD patients, associated with a strong infiltrate of CD68 + /H-ferritin + cells. Furthermore, a correlation between the levels of H-ferritin as well as of the number of CD68 + /H-ferritin + cells and the multi-visceral involvement of the disease was observed. Graphical Abstract: